2014
DOI: 10.4103/1305-7456.130608
|View full text |Cite
|
Sign up to set email alerts
|

Dental arch asymmetry

Abstract: Objective:This study was conducted to assess the dental arch asymmetry in a Yemeni sample aged (18-25) years.Materials and Methods:The investigation involved clinical examination of 1479 adults; only 253 (129 females, 124 males) out of the total sample were selected to fulfill the criteria for the study sample. Study models were constructed and evaluated to measure mandibular arch dimensions. Three linear distances were utilized on each side on the dental arch: Incisal-canine distance, canine-molar distance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…The results in the present study reported larger mean values of both maxillary and mandibular arches width at IFMD, ISMD in addition to mandibular ICD in boys than in girls, these findings are in line with those obtained in other studies (21,24,58,59) .Furthermore this study revealed that the length of maxillary and mandibular dental arches among boys were larger in all dimensions mean values than girls, this in accordance with other studies (17,60) . This might be attributed to the smaller and smoother bony ridge and alveolar processes in girls than in boys and due to physical characteristics and strongest musculature in males which play role in facial development (19,60) . While the findings of the current study were in disagreement with other studies which concluded that there were no such differences between genders in the dental arches (36,61) , this disagreement could be due to ethnic differences, sample size and /or selection criteria.…”
Section: Discussionsupporting
confidence: 93%
“…The results in the present study reported larger mean values of both maxillary and mandibular arches width at IFMD, ISMD in addition to mandibular ICD in boys than in girls, these findings are in line with those obtained in other studies (21,24,58,59) .Furthermore this study revealed that the length of maxillary and mandibular dental arches among boys were larger in all dimensions mean values than girls, this in accordance with other studies (17,60) . This might be attributed to the smaller and smoother bony ridge and alveolar processes in girls than in boys and due to physical characteristics and strongest musculature in males which play role in facial development (19,60) . While the findings of the current study were in disagreement with other studies which concluded that there were no such differences between genders in the dental arches (36,61) , this disagreement could be due to ethnic differences, sample size and /or selection criteria.…”
Section: Discussionsupporting
confidence: 93%
“…Al-Zubair and Agrawal et al, reported that the mandibular dimension was considered asymmetric when the difference between the two sides was more than 2-3 mm, while Gribel BF et al also reported that the left and right mandibular differences of 4-5 mm was still considered as a normal asymmetry of face dimensions. 29,30 Some researches reveal that facial asymmetry is more common to occur on the right side with the same distribution between males and females. 31,32 This condition is probably because the growth on the right side of the face is more dominant than that of the left side; it happens to the larger brain dimensions on the right side as well.…”
Section: Discussionmentioning
confidence: 99%
“…Arches of healthy persons with full natural dentitions usually show only negligible asymmetry [67]. In malocclusion cases, dental and facial asymmetries are more frequently observed and more pronounced [68,69].…”
Section: Bilateral Symmetry Of Dental Arches and Jawsmentioning
confidence: 99%